Secure Pesticide Storage: Workspace Features of a Pesticide Storage Facility - Thomas W. Dean (EDIS)
This document identifies and discusses three key features of a pesticide storage facility's interior that, in combination, promote both worker safety and pesticide container security. This document is Fact Sheet PI-31, part of a series from the Pesticide Information Office, Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 2004. Revised: November 2004.